Special Fresno City Council Swearing-In Session in Wine Room at Valdez Hall - Watkins, Howard::::::::: (1983)
Channel 24 TV reporter Jack Noldon interviewing Les Kimber with Chris Petersen In background: Joe Williams talking with Deran Koligian